CCDM model with spatial curvature and the breaking of dark degeneracy - Jesus, J. F. [UNESP] (2016)
Creation of Cold Dark Matter (CCDM), in the context of Einstein Field Equations, leads to a negative creation pressure, which can be used to explain the accelerated expansion of the Universe. Recently, it has been shown that the dynamics of expansion of such models can not be distinguished from the concordance Lambda CDM model, even at higher orders in the evolution of density perturbations, leading at the so called dark degeneracy. However, depending on the form of the CDM creation rate, the inclusion of spatial curvature leads to a different behavior of CCDM when compared to Lambda CDM, even at background level. With a simple form for the creation rate, namely, Gamma proportional to 1/H, we show that this model can be distinguished from Lambda CDM, provided the Universe has some amount of spatial curvature. Observationally, however, the current limits on spatial flatness from CMB indicate that neither of the models are significantly favored against the other by current data, at least in the background level.